Nutrition for healthy living - Schiff, Wendy. (McGraw-Hill, 2016)
Completely revised, up-to-date, and redesigned, the fourth edition of Nutrition for Healthy Living takes an innovative approach to introductory nutrition for non-science majors. With its unique, concise organization and a distinct focus on consumerism, this engaging, fun-to-read text provides students with the scientific foundation needed to make informed nutritional decisions well beyond the classroom.